Pengaruh Efikasi Diri dan Dukungan Keluarga Terhadap Perencanaan Karier Siswa SMK Negeri 6 Surakarta - Winda Supriyatin; Cicilia Dyah Sulistyaningrum Indrawati; Nur Rahmi Akbarini (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to determine the effect of self-efficacy and family support variables, partially and simultaneously, on student’s career planning. This research is quantitative with correlational method. The population of this research is class XII students of SMK N 6 Surakarta totaling 516 students. This study used proportionate random sampling technique. This study used questionnaire for data collection and data analysis techniques using classical assumption tests and multiple linear regression techniques supported by IBM SPSS 26. The results showed that: (1) there was a positive and significant effect of self-efficacy on career planning, as evidenced by the significance value of 0.000 <0.05 and the tcount value of 7.765 > t table 1.970 and; (2) there was a positive and significant effect of family support on career planning, as evidenced by the significance value of 0.000 <0.05 and the t value of 7.287 > t table 1.970; and (3) there was a positive and significant effect of self-efficacy and family support simultaneously on career planning, as evidenced by the significance value of 0.000 <0.05 and a F value of 82.970> F table 3.04. The results of this study indicate that the effective contribution simultaneously amounted to 42.8% and the remaining 57.2% was influenced by other factors not included in this study.